Food Vloggers, Digital Marketing and Culinary Purchase Satisfaction - Ni Komang Netriani (Green Publisher Indonesia, 2024)
Rapid technological developments have changed the way businesses are run, with digital marketing through social media becoming increasingly important. In Indonesia, social media plays a big role in purchasing decisions, supported by the high number of users reaching 167 million in 2023. This study explores the impact of food vloggers, digital marketing, and customer trust on consumer buying interest and decisions at Becol Serangan Restaurant and Pan Kuncung Restaurant in Denpasar, Bali. With the Theory of Planned Behavior (TPB) approach, this study uses a sample of 96 respondents collected through an online survey. The results of the study show that food vloggers, digital marketing, and customer trust have a positive and significant influence on buying interest and purchase decisions. In addition, buying interest also mediates the influence of food vloggers and digital marketing on purchasing decisions. This shows that effective promotion through food vloggers and digital marketing, as well as high trust from customers, can increase consumer buying interest and purchasing decisions. The results of this study underscore the importance of the right marketing strategy and customer trust in influencing consumer behavior, especially in the culinary industry in Bali.